Effects of two different contact lenses on ocular physiological parameters and tear function tests - Ugurlu,Adem (2019)
Abstract Objective: To investigate the effects of two types of contact lenses made of two different types of silicone hydrogel material on ocular physiological parameters and tear function tests. Methods: The contact lenses with the appropriate diopters were supplied to the volunteering patients. The patients were evaluated before wearing the contact lenses (visit0:V0), at the first month(visit1:V1) and at the thirth month(visit2:V2) following their wear. At all visits a detailed biomicroscopic examination was done, ocular physiological variables were collected, the tear function tests were performed and the tear meniscus area (TMA) was visualized and measured with anterior segment optical coherence tomography (AS-OCT). Results: The results of Schirmer 1 test were 12.07 ± 1.51 [9-16] mm for the right eyes (samfilcon A group) and 12.09 ± 1.5 [9-16] mm for the left eyes (senofilcon A group) at V0. (p=0.950) At V2, the mean Schirmer 1 test results were 11.92±1.34 [9-15] mm in the samfilcon A group and 12.2±1.41 [9-16] mm in the senofilcon A group (p=0.239). The mean TMA dimensions in the AS-OCT images were 338.42±47.1 [241-401] microns in the samfilcon A group and 338.42±47.1 [241-401]microns in the senofilcon A group at V0. (p>0.05). At V2, the mean TMA dimensions were 337.2±45.53 [241-402] microns in thesamfilcon A group and 340.31±48.22 [240-411] microns in the senofilcon A group (p=0.728). Conclusions: Our study has demonstrated that contact lenses containing samfilcon A and senofilcon A silicone hydrogel material do not cause meaningful ocular surface problems.